2012 IEEE/RSJ International Conference on Intelligent Robots and Systems 2012
DOI: 10.1109/iros.2012.6385904
|View full text |Cite
|
Sign up to set email alerts
|

The Milli-Motein: A self-folding chain of programmable matter with a one centimeter module pitch

Abstract: Abstract-The Milli-Motein (Millimeter-Scale Motorized Protein) is a chain of programmable matter with a 1 cm pitch. It can fold itself into digitized approximations of arbitrary threedimensional shapes. The small size of the Milli-Motein segments is enabled by the use of our new electropermanent wobble stepper motors, described in this paper, and by a highly integrated electronic and mechanical design. The chain is an interlocked series of connected motor rotors and stators, wrapped with a continuous flex circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…4,5 Self-folding origami techniques 6 can automate the folding process of lightweight structures. The reconfigurable modular robot 7 and programmable structures 8,9 are also approaches that can potentially provide a customized robotic system with minimum assembly processes. New fabrication techniques have been developed for printable components such as instant circuits, 10 printable batteries, 11 and printable optics.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Self-folding origami techniques 6 can automate the folding process of lightweight structures. The reconfigurable modular robot 7 and programmable structures 8,9 are also approaches that can potentially provide a customized robotic system with minimum assembly processes. New fabrication techniques have been developed for printable components such as instant circuits, 10 printable batteries, 11 and printable optics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to illustrate the advantages of our system composed of cells with non-uniform softness settings, we also run the algorithm with uniform softness settings (which is the case in state-of-the-art systems [6][7][8][9][10]). This result is also plotted in Figure 4(b).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, this work was extended to three dimensions, along with algorithms to approximate any three dimensional shape [7]. Inspired by this work, Knaien et al [8] developed a system called "MilliMoteins" that consisted of a chain of electropermanent magnetic motors that could dynamically fold into different configurations. In another work [9], it was shown that serially connected soft cubes could selfassemble into a previously designed 3-D shape by being stretched by an external tension.…”
Section: Introductionmentioning
confidence: 99%
“…Selfassembling modular robots [23][24][25][26] can achieve the same function by injecting each module into a workspace one by one and then assembling themselves into a desired shape. However, most self-folding and self-assembling robots require onboard power and controller for their final configuration, 19,20,25 making them unavailable at microscale. For those that no onboard power and controller are required, their self-assembly usually depends on their response to the change in physical conditions such as tempeature 26 or magnetic field.…”
Section: Introductionmentioning
confidence: 99%